RNAi targeting of rootworm Troponin I transcripts confers root protection in maize. (January 2019) - Fishilevich, Elane; Bowling, Andrew J.; Frey, Meghan L.F.; Wang, Po-Hao; Lo, Wendy; Rangasamy, Murugesan; Worden, Sarah E.; Pence, Heather E.; Gandra, Premchand; Whitlock, Shannon L.; Schulenberg, Greg; Knorr, Eileen; et al.
Abstract: Western corn rootworm, Diabrotica virgifera virgifera, is the major agronomically important pest of maize in the US Corn Belt. To augment the repertoire of the available dsRNA-based traits that control rootworm, we explored a potentially haplolethal gene target, wings up A (wupA), which encodes Troponin I. Troponin I, a component of the Troponin-Tropomyosin complex, is an inhibitory protein involved in muscle contraction. In situ hybridization showed that feeding on wupA -targeted dsRNAs caused systemic transcript knockdown in D. v. virgifera larvae. The knockdown of wupA transcript, and by extension Troponin I protein, led to deterioration of the striated banding pattern in larval body muscle and decreased muscle integrity. Additionally, the loss of function of the circular muscles surrounding the alimentary system led to significant accumulation of food material in the hind gut, which is consistent with a loss of peristaltic motion of the alimentary canal. In this study, we demonstrate that wupA dsRNA is lethal in D. v. virgifera larvae when fed via artificial diet, with growth inhibition of up to 50% within two days of application. Further, wupA hairpins can be stably expressed and detected in maize. Maize expressing wupA hairpins exhibit robust root protection in greenhouse bioassays, with several maize transgene integration events showing root protection equivalent to commercial insecticidal protein-expressing maize. Graphical abstract: Image 1 Highlights: Diet-applied WupA dsRNA leads to rapid growth inhibition and lethality in the western corn rootworm. WupA dsRNA leads to systemic knockdown of wupA transcript in rootworm. Phenotypes of wupA dsRNA include loss of Z-band pattern in body wall muscles and accumulation of material in the hind gut. Maize plants expressing wupA hairpins show robust root protection from rootworm in the greenhouse. Root-protected maize accumulate intact wupA RNA hairpins in plant tissues.